The Trinidad and Tobago corporate social responsibility review 2012 - 2013- (Virtually Yours T & T Port of SpainTT, 2013)
Reports on corporate social responsibility strategies employed by businesses in Trinidad and Tobago, includes human-interest stories which reaffirm the value of CSR.
Keywords: SOCIAL WELFARE